2011
DOI: 10.3148/72.2.2011.77
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Intake in: Clients with Chronic Wounds

Abstract: To assess relationships among food intake, anthropometrics, and wound severity, we studied 31 home care clients with pressure ulcers (PUs) or venous stasis ulcers (VSUs). Anthropometric variables (weight, height, waist circumference [WC]) were measured according to standard methodologies. Risk for PU development was assessed using the Braden Pressure Ulcer Risk Assessment score and wound severity according to the National Pressure Ulcer Advisory Panel. Three-day food records were analyzed to assess dietary ade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 24 publications
0
15
0
4
Order By: Relevance
“…All participants had ulcers classified by the CEAP classification as C5 or C6. Six studies reported patient comorbidities, which included diabetes mellitus, arterial hypertension, chronic heart failure and cardiovascular disease (Abbade et al., , ; Apollonio et al., ; Legendre et al., ; McDaniel et al., ; Wojcik et al., ). Sample sizes of included studies were generally small with a median size of 84, ranging from 2 to 639.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…All participants had ulcers classified by the CEAP classification as C5 or C6. Six studies reported patient comorbidities, which included diabetes mellitus, arterial hypertension, chronic heart failure and cardiovascular disease (Abbade et al., , ; Apollonio et al., ; Legendre et al., ; McDaniel et al., ; Wojcik et al., ). Sample sizes of included studies were generally small with a median size of 84, ranging from 2 to 639.…”
Section: Resultsmentioning
confidence: 99%
“…In eight of the 13 studies reporting weight status, the majority of VLU patients were found to have a BMI >25 (Table ) (Abbade et al., , ; Finlayson et al., ; McDaniel et al., ; Serra et al., ; Tobon et al., ; Vines et al., ; Wojcik et al., ). Of the seven studies that measured obesity exclusively, prevalence ranged from 21.8‐81.8% of participants (Abbade et al., ; Apollonio et al., ; De Franciscis et al., ; Legendre et al., ; McDaniel et al., ; Tobon et al., ; Vines et al., ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations